Agrochemicals and horticulturists: the invisible risks inserted in food produced in Natuba – Vitoria de Santo Antão/PE | Agroquímicos e horticultores: os riscos invisíveis inseridos nos alimentos produzidos em Natuba - Vitoria de Santo Antão / PE - Noronha, Cartiele Rosale Borges; Lira, Elizabete Buonora de Souza; Morais, Alex Souza (Revista Geama, 2016)
The indiscriminate use and contamination by pesticides are subjects of research that has attracted attention in view of its consequences for human health and the risks of environmental degradation. The study site was the Community of Naturaliste, in the municipality of Vitoria de Santo Antao - PE, one of the largest producers of leafy vegetables state. The objective of this study is to analyze research on the use of pesticides in vegetable production in this community, pointing out the main risks generated during this production chain, from its deployment to consumption. As methodological procedure, the literature and documentary studies of Agricultural Production Process in Naturaliste has been used. The methodologies used in the research material were qualitative and quantitative analysis through questionnaires; Lifting primary and secondary indicators; collection of soil samples, water, some vegetables in the field and blood collections in farmers. The main results show the possibility of various risks of environmental pollution and harmful to human health, not favoring the quality of food consumed by the analyzed production chain and other risks inherent in the production process. It follows that many production practices should be replaced with agroecological models, seeking harmony between the need for food production and the availability of natural resources, with emphasis on the social, cultural, environmental and ethical factors.